1987
DOI: 10.1002/path.1711530107
|View full text |Cite
|
Sign up to set email alerts
|

Gastric submucosal tumours of neurogenic origin with neuroaxonal and schwann cell elements

Abstract: Twelve cases of gastric submucosal tumours, originally diagnosed as leiomyoma and leiomyosarcoma, were investigated by staining with the neurogenic markers S-100 and neuron specific enolase (NSE). Three cases were, in addition, studied by electron microscopy. The tumours stained negatively for desmin, indicating that they were not of smooth muscle origin. All stained positively for S-100 and NSE. The ultrastructural features in the cases examined by electron microscopy were reminiscent of autonomic nerve struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
20
0
3

Year Published

1991
1991
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 18 publications
0
20
0
3
Order By: Relevance
“…In the majority of our cases the ultrastructural and immunohistochemical findings allow us the distinction between GAN and smooth muscle tumours; a source of difficulty is to differentiate between them and Schwann cell tumours. The presence of electron dense granules in dendritic prolongations indicates neuroaxonal differentiation [27]. Our cases do not display features which are considered to be hallmarks of schwannian differentiation such as continuous basal lamina, mesoaxonal structures and long-spaced collagen.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…In the majority of our cases the ultrastructural and immunohistochemical findings allow us the distinction between GAN and smooth muscle tumours; a source of difficulty is to differentiate between them and Schwann cell tumours. The presence of electron dense granules in dendritic prolongations indicates neuroaxonal differentiation [27]. Our cases do not display features which are considered to be hallmarks of schwannian differentiation such as continuous basal lamina, mesoaxonal structures and long-spaced collagen.…”
Section: Discussionmentioning
confidence: 79%
“…Our cases do not display features which are considered to be hallmarks of schwannian differentiation such as continuous basal lamina, mesoaxonal structures and long-spaced collagen. However, Yagigashi et al [27] describe a distinctive neurogenic tumour of the stomach composed of neuroaxonal and schwannian elements suggesting they probably arise from a combination of Schwann cells and ganglion cells. These tumours display mesoaxonal structures containing microtubules, microfilaments and small electron-dense granules (some of them considered to be lysosomes).…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical studies confirmed that not only do GISTs lack features of smooth muscle cells [18][19][20], but GISTs also possess characteristics of neural cells [21,22]. Therefore, a more accurate means of identifying GIST was needed.…”
mentioning
confidence: 80%
“…As this wider spectrum has emerged, the term gastrointestinal stromal tumors (GIST) has been applied with increasing frequency to this group of differentiated and undifferentiated tumors in humans. 1,13,19,22,25,37 This term has re-*Deceased.…”
mentioning
confidence: 99%